2019
DOI: 10.1111/jspn.12281
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the occurrence of neonatal procedural pain

Abstract: Objectives The objective of this study was to describe the occurrence of neonatal procedural pain and explore the factors that influence the frequency of painful procedures. Design A descriptive prospective epidemiologic study. Setting NICU at a general hospital in China. Methods A demographic and diagnosis or illness information questionnaire and an occurrence of procedural pain questionnaire specifically designed for this study were used to record the current status of neonatal procedural pain. The neonatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
1
7
2
Order By: Relevance
“…Three hundred twenty‐five neonates experienced a total of 1325 skin breaking and non‐skin breaking painful procedures, corresponding to an average of 4.2 per day in each neonate in the first 24 hours of NICU admission, which is similar to four procedures per day, studies done in Kenya 3 . Inconsistent with our findings, previous studies conducted in different countries reported that each neonate experienced an average of 7 to 13 painful procedures per day 2,4,6,9 . Another systemic review of observational study 1 also reported an average of 7.5 to 17.3 per neonate per day.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Three hundred twenty‐five neonates experienced a total of 1325 skin breaking and non‐skin breaking painful procedures, corresponding to an average of 4.2 per day in each neonate in the first 24 hours of NICU admission, which is similar to four procedures per day, studies done in Kenya 3 . Inconsistent with our findings, previous studies conducted in different countries reported that each neonate experienced an average of 7 to 13 painful procedures per day 2,4,6,9 . Another systemic review of observational study 1 also reported an average of 7.5 to 17.3 per neonate per day.…”
Section: Discussionsupporting
confidence: 80%
“…[1][2][3][4] The most frequently performed painful procedures were heel lance, suctioning, venipuncture, and peripheral IV insertion. [5][6][7][8][9] Despite the misconception regards to neonatal pain in the past years, scientific evidence indicates that pain pathways are active and functional as early as 25 weeks of gestation. 10 Under-treated pain experienced in the early life of the neonatal period can cause physiological and behavioral changes, which may lead to detrimental long-term consequences of altered pain sensation, neuro-behavioral changes, and learning disabilities in later life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, each preterm infant experienced 20 skin punctures as painful operations during the mean 14.2-day NICU stay, which translates to 1.4 skin punctures per day. Compared with the frequencies, 5 [ 30 ] and 10 [ 31 ] painful operations, for each infant per day in previous studies, we found that the average frequency of painful operations in this cohort was lower due to the lack of records of repeated punctures. We found that infants with a shorter LOS were likely to perform better in the weight status at 40 weeks corrected age.…”
Section: Discussioncontrasting
confidence: 78%
“…Experts in neonatal pain management agree that endotracheal intubation can be classified as moderate to severely painful 3 . Repeated painful stimuli cause several short and long-term adverse effects on newborns 4 . The hypothalamic–pituitary–adrenal axis (HPA axis) is an essential endocrine axis of the human body, with cortisol being its primary end product.…”
Section: Introductionmentioning
confidence: 99%